Identity Politics and Decolonising the Construct of ‘South Asia’ - Cheema, Khola Iftikhar; Ahmad, Tohid (Progressive Research Journal of Arts & Humanities (PRJAH), 2025)
Colonialism not only affected the economy and political structures of the colonised regions, but it also had long-term impacts in shaping and re-shaping the identities of those regions and the people. The colonial rulers saw everything indigenous through the Western lens and tried to simplify it to control and govern. For similar purposes, the colonial rulers tried to erase the multiplicity of identities in the region deliberately and labelled it as ‘South Asia’ and used it as a tool to simplify governance over the region’s vast and diverse populations. In this way, colonials not only strengthen their control over the region but also try to change the cultural map of the region. This paper will explore how the term ‘South Asia’ originated and became so popular. This paper also explores how the colonial rulers tried to shape the region’s identity through the Western perceptions of the region, presenting it as a monolithic, exotic, and often inferior in culture through the tools such as modern education, census politics, bureaucratic correctness and oriental historiography.